Cryogel Addition Effect on Ultrasound-Assisted Thawing of Pork Meat - Jonathan Coria-Hernández; Rosalía Meléndez-Pérez (International Journal of Food Science)
The use of new technologies that allow for improving conventional food preservation processes is what the industry has been adopting in recent decades, with high-intensity ultrasound (US) and the application of cryoprotectant agents (cryogels) being those that have become more relevant today. For this reason, in this study, cuts of Longissimus thoracis pork frozen in liquid nitrogen with and without waxy starch cryogel and thawed under controlled conditions in water immersion and with US were used, evaluating thermal parameters such as the initial zone and the melting rate of ice crystals and quality parameters such as pH, water holding capacity (WHC), microstructure, color profile, shear force, and surface changes. It was shown that the addition of cryogel modifies the initial fusion zone, that US-assisted thawing increases the fusion rate, and that both factors influence the quality parameters. However, the main effect on pH is the use of cryogel, unlike WHC, color parameters, and shear force, where the main impact is the thawing method. These results conclude that waxy starch cryogel and the US at 50% thawing have the potential to apply assistance technology in food processing.